The impact of electronic banking on profitability and market share: Evidence from banking industry - Mohammad Khodaei Valahzaghard; Elham Bagherzadeh Bilandi (Management Science Letters)
This paper presents an empirical investigation to study the effects of electronic banking devices such as automated telling machines (ATM), Point of sales (POS) and Pin Pad on profitability and market share in Iranian banking industry. The population of this study considers the information of 16 banks, five governmental and eleven private, over the period 2007-2012. Using two regression techniques, the study has detected that while Pin Pad may influence on return of assets positively, ATM and POS may not have any meaningful impact on profitability. Moreover, in our survey, none of technological facilities had a meaningful impact on market share but there was a positive and meaningful relationship between bank size and market share.